2022
DOI: 10.21203/rs.3.rs-1598386/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A positive feedback loop controls Toxoplasma chronic differentiation

Abstract: Successful infection strategies must balance pathogen amplification and persistence. In Toxoplasma gondii, this is accomplished through differentiation into dedicated cyst-forming chronic stages that avoid clearance by the host immune system. The transcription factor BFD1 is both necessary and sufficient for stage conversion; however, its regulation is not understood. We examine five factors transcriptionally activated by BFD1. One of these is a cytosolic RNA-binding protein of the CCCH-type zinc finger family… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Reassuringly, while this manuscript was under review, Licon et al (bioRxiv preprint) identified TGME49_311100 (named BFD2) as an important regulator that intersects with BFD1. Loss of BFD2 reduces BFD1 protein levels and compromise the parasites' ability to fully differentiate in vitro and in mice 57 . Given that BFD2 controls BFD1 expression (only present in bradyzoites) and that PP2A is essential for BFD2 dephosphorylation, further investigation of PP2A-BFD2-BFD1 connection may illustrate the mechanisms that govern complex spatially and temporally regulated molecular events occurring during tachyzoite-to-bradyzoite differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Reassuringly, while this manuscript was under review, Licon et al (bioRxiv preprint) identified TGME49_311100 (named BFD2) as an important regulator that intersects with BFD1. Loss of BFD2 reduces BFD1 protein levels and compromise the parasites' ability to fully differentiate in vitro and in mice 57 . Given that BFD2 controls BFD1 expression (only present in bradyzoites) and that PP2A is essential for BFD2 dephosphorylation, further investigation of PP2A-BFD2-BFD1 connection may illustrate the mechanisms that govern complex spatially and temporally regulated molecular events occurring during tachyzoite-to-bradyzoite differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We additionally profiled transcriptomic remodeling in PKA C3-AID parasites that had been depleted of the kinase for 24 h and compared these changes to the chronic-stage transcriptome of parasites overexpressing BFD1 (Waldman et al, 2020). We observed up-regulation of several chronic-stage proteins upon PKA C3 depletion ( Figure 6I ), including BAG1, CST1, CST10, MIC13, and Tg SPT2 (Licon et al, 2023). PKA C3 mRNA abundance was down-regulated, suggesting that tagging may alter steady-state transcript levels.…”
Section: Resultsmentioning
confidence: 94%
“…Although a massive analysis of gene expression is necessary to detect specific changes, part of the study shows that the expression of Rop5 and Rop18 does not occur at the transcriptional level, but rather posttranscriptionally, affecting their translation. This regulation could be given by the presence of non-coding RNAs (ncRNAs) and there is increasing evidence for a significant role for pos-transcriptional mechanisms [65,66]. Future studies should take this possibility into account, considering a possible role of H2B.Z acetylation, to analyze ncRNAs expression in T. gondii.…”
Section: Discussionmentioning
confidence: 99%